2014
DOI: 10.4049/jimmunol.1400699
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Lysophosphatidylcholine by Type II NKT Cells and Protection from an Inflammatory Liver Disease

Abstract: Summary Lipids presented by the major histocompatibility complex (MHC) class I-like molecule, CD1d, are recognized by natural killer T (NKT) cells, which can be broadly categorized into two subsets. The well-characterized type I NKT cells, express a semi-invariant T cell receptor (TCR) and can recognize both α- and β-linked glycolipids, whereas type II NKT cells are less well studied, express a relatively diverse TCR repertoire, and recognize β-linked lipids. Recent structural studies have shown a distinct mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…Although, some studies indicated that LPC might activate NKT cells3031, but, the present study is the first in vivo report regarding activation of NKT cells by LPC in case of allergic airway disease. The down regulation of allergic airway disease parameters was due to blockage of CD1d-NKT signalling and not due to depletion of APCs2122.…”
Section: Discussionmentioning
confidence: 63%
“…Although, some studies indicated that LPC might activate NKT cells3031, but, the present study is the first in vivo report regarding activation of NKT cells by LPC in case of allergic airway disease. The down regulation of allergic airway disease parameters was due to blockage of CD1d-NKT signalling and not due to depletion of APCs2122.…”
Section: Discussionmentioning
confidence: 63%
“…NKT cells have been shown to play either a pathogenic or protective role in inflammatory liver disease [32, 33]. However, most of these studies used a model of ConA-induced hepatitis which causes acute liver inflammation but does not reflect chronic disease seen in human AIH.…”
Section: Discussionmentioning
confidence: 99%
“…32 The sulphatide-reactive vNKT cells also reacted with other self-lipids, including b-GlcCer and b-GalCer, 33 as well as with lysophospholipids such as lysophosphatidylcholine. 34 The TCRs of vNKT cells interact with CD1d-glycolipid complexes in a perpendicular manner and predominantly engage the ligand using the b-chain rather than the a-chain. 35 Like iNKT cells, vNKT cells develop in the thymus, with a requirement for CD1d expression by haematopoietic cells, as well as the adaptor protein SAP and the transcription factor promyelocytic leukaemia zinc finger.…”
Section: 25mentioning
confidence: 99%
“…8,29 Sulphatide and lysophosphatidylcholine also suppress concanavalin A-induced hepatitis mediated by iNKT cells. 34,39 Tools and experimental models to study NKT cells Because markers expressed by NKT cells are not uniquely expressed by these cells, multimeric CD1d molecules loaded with glycolipid antigens have been extensively employed to identify these cells. CD1d/a-GalCer-tetramers specifically identify iNKT cells, 40 whereas CD1d/sulphatide-tetramers interact with sulphatide-specific vNKT cells.…”
Section: 25mentioning
confidence: 99%